Modeling of Engineering Student Satisfaction - Zainol, Mustafa; Norbayani, Basri; Norkisme, Zainal Abidin; Nur Riza, Mohd Suradi; Zalina, Mohd Ali; Faridatul Azna, Ahmad Shahabudin; M. R., Abdul Hamid (Science Publisher, 2012)
The purpose of this study is first; to identify the antecedents to student satisfaction and the relationship between student satisfaction and promotion. Second; to develop a suitable student satisfaction model considering the antecedents of student satisfaction with student satisfaction and promotion for students of engineering in universities in Malaysia. A total of 500 engineering students from University Kebangsaan Malaysia (UKM), University Putra Malaysia (UPM), University Islam Antarabangsa Malaysia (UIAM), University Malaya (UM) and University Tenaga Nasional (UNITEN) were involved as respondents in this research. Approach: To examine these relationships, a model from past study on student satisfaction of Applied Sciences students in Austria was referred. Based on this model, a suitable model measuring student satisfaction of engineering students in Malaysia is constructed. Structural equation modeling is used as its capability in testing the combination of relationship between service performance, university performance, relationship, university standing, student satisfaction and promotion in higher education simultaneously. Results: Suitable model which is able to explain the factors linked to student satisfaction in engineering education is established. Conclusion: This study finds that the antecedent factors have a direct effect on student satisfaction and also student satisfaction has a significant effect on promotion.